Societal Stigma Towards Patients with Mental Disorders in A Sociocultural Context: Literature Review - Indra Maulana; Hesti Platini (Indonesian Journal of Global Health Research, 2025)
Stigma towards people with mental disorders (ODGJ) is a complex global issue that has a negative impact on patient well-being, access to health services, and their healing process and social integration. This stigma includes various forms of discrimination, stereotypes, and prejudices that can significantly hinder effective treatment of mental disorders. This study aims to provide a comprehensive picture of the stigma of people with mental disorders in various socio-cultural contexts. The literature reviewed in this study explores how stigma is formed, the factors that influence it, and the impact on individuals and communities. This study uses a literature review method by examining scientific articles that discuss the stigma of people with mental disorders in various regions of Indonesia in less than the last 10 years. Results: Data analysis shows that the stigma of people with mental disorders is still quite high, although there is variation between regions and community groups. The results of the study show that stigma against ODGJ is still widely found in Indonesian society. This stigma is influenced by various factors, such as lack of knowledge about mental disorders, cultural values, and social norms. This stigma can have negative impacts on PLWH, such as discrimination, social isolation, and barriers in accessing health services. Increasing public knowledge and understanding of mental disorders through education and public campaigns, as well as culturally sensitive interventions, can help reduce stigma and improve the quality of life of patients with mental disorders. The importance of understanding the stigma picture in this sociocultural context cannot be overstated because interventions designed to reduce stigma must be tailored to local conditions to be effective.